Progressive loss of corneal nerve fibers is associated with physical inactivity and glucose lowering medication associated with weight gain in type 2 diabetes. Issue 10 (20th June 2022) - Ponirakis, Georgios; Al‐Janahi, Ibrahim; Elgassim, Einas; Gad, Hoda; Petropoulos, Ioannis N; Khan, Adnan; Ali, Hamda; Siddique, Mashhood A; Gul, Wajiha; Ferdousi, Maryam; Kalteniece, Alise; Mohamed, Fatima FS; et al.
Abstract: Aims/Introduction: Limited studies have identified risk factors linked to the progression of diabetic peripheral neuropathy (DPN) in type 2 diabetes. This study examined the association of risk factors with change in neuropathy measures over 2 years. Materials and Methods: Participants with type 2 diabetes ( n  = 78) and controls ( n  = 26) underwent assessment of clinical and metabolic parameters and neuropathy using corneal confocal microscopy (CCM), vibration perception threshold (VPT), and the DN4 questionnaire at baseline and 2 year follow‐up. Results: Participants with type 2 diabetes had a lower corneal nerve fiber density (CNFD), branch density (CNBD), and fiber length (CNFL) ( P  ≤ 0.0001) and a higher VPT ( P  ≤ 0.01) compared with controls. Over 2 years, despite a modest reduction in HbA1c ( P  ≤ 0.001), body weight ( P  ≤ 0.05), and LDL ( P  ≤ 0.05) the prevalence of DPN ( P  = 0.28) and painful DPN ( P  = 0.21) did not change, but there was a significant further reduction in CNBD ( P  ≤ 0.0001) and CNFL ( P  ≤ 0.05). CNFD, CNBD, and CNFL decreased significantly in physically inactive subjects ( P  < 0.05–0.0001), whilst there was no change in CNFD ( P  = 0.07) or CNFL ( P  = 0.85) in physically active subjects. Furthermore, there was no change in CNFD ( P  = 0.82), CNBD ( P  = 0.08), or CNFL ( P  = 0.66) in patients treated with glucose lowering medication associated with weight loss, whilst CNBD ( P  = 0.001) decreased in patients on glucose lowering medication associated with weight gain. Conclusions: In participants with type 2 diabetes, despite a modest improvement in HbA1c, body weight, and LDL there was a progressive loss of corneal nerve fibers; except in those who were physically active or on glucose lowering medication associated with weight loss.